2013
DOI: 10.1021/ac3034807
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Isotope Abundance Variations in Nature by Gravimetric Spiking Isotope Dilution Analysis (GS-IDA)

Abstract: Subtle variations in the isotopic composition of elements carry unique information about physical and chemical processes in nature and are now exploited widely in diverse areas of research. Reliable measurement of natural isotope abundance variations is among the biggest challenges in inorganic mass spectrometry as they are highly sensitive to methodological bias. For decades, double spiking of the sample with a mix of two stable isotopes has been considered the reference technique for measuring such variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Both studies used Nd isotopic standards doped with variable amounts of Sm to replicate the likely natural range of Sm/Nd, and formulated a relationship between the exponential mass bias coefficients to correct the isobaric 144 Sm interference. Reported errors on 143 Nd/ 144 Nd and 147 Sm/ 144 Nd were similar for the two studies, and were roughly equivalent to measurements made by conventional methods. Sanchez-Lorda et al 157 reported that 147 Sm/ 144 Nd reproducibility ranged from 0.2% to 0.7%, which is slightly higher than for IDA measurements.…”
Section: Stable Isotope Fractionationsupporting
confidence: 62%
See 2 more Smart Citations
“…Both studies used Nd isotopic standards doped with variable amounts of Sm to replicate the likely natural range of Sm/Nd, and formulated a relationship between the exponential mass bias coefficients to correct the isobaric 144 Sm interference. Reported errors on 143 Nd/ 144 Nd and 147 Sm/ 144 Nd were similar for the two studies, and were roughly equivalent to measurements made by conventional methods. Sanchez-Lorda et al 157 reported that 147 Sm/ 144 Nd reproducibility ranged from 0.2% to 0.7%, which is slightly higher than for IDA measurements.…”
Section: Stable Isotope Fractionationsupporting
confidence: 62%
“…De-convolution using a double spike to give bias-free isotope ratios requires an element with a minimum of four accurately measurable isotopes in the natural or the with-spike mixture. However, by using gravimetric mixing of the sample with different proportions of an isotopic spike, Chew and Walczyk 143 have developed a modication of the double spike technique capable of highprecision IR measurements using only three isotope signals. This gravimetric spiking IDA (GS-IDA) approach has the potential to increase the precision of Mg isotope ratios, beneting studies of metabolism in humans and elemental diffusion in mineral species.…”
Section: Double-spike Systematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…82 Also linked to the modelling of bone disorders (plus coronary artery disease), Mg isotopes can now be analysed by TIMS using a gravimetric mix of sample and spike. 83 This unusual technique is necessary, since Mg is made up of three stable isotopes only, and is thus unsuitable for the double-spike method. A general review of the TIMS analysis of additional stable isotopes (such as Zn, Cu, Fe, Ca, Mo) in understanding human and animal metabolism is provided by Turnland.…”
Section: Applications In Life Sciencesmentioning
confidence: 99%
“…Drawbacks for obtaining absolute isotope ratios are the application of fractionation models and the required accurate quantification of the element amount in the sample and the doublespike. Additionally, this technique can be applied only to elements with at least four isotopes; with the addition of a second blend also elements with three isotopes are accessible [5]. A completely different approach in TIMS is the total evaporation technique, which has been developed for the measurement of U and Pu first.…”
Section: Introductionmentioning
confidence: 99%